Long‐term recovery from opioid use disorder: recovery subgroups, transition states and their association with substance use, treatment and quality of life. - Craft, William H.; Shin, Hwasoo; Tegge, Allison N.; Keith, Diana R.; Athamneh, Liqa N.; Stein, Jeffrey S.; Ferreira, Marco A. R.; Chilcoat, Howard D.; Le Moigne, Anne; DeVeaugh‐Geiss, Angela; Bickel, Warren K. (Addiction, 2023)
Background and Aims: Limited information exists regarding individual subgroups of recovery from opioid use disorder (OUD) following treatment and how these subgroups may relate to recovery trajectories. We used multi‐dimensional criteria to identify OUD recovery subgroups and longitudinal transitions across subgroups. Design, Setting and Participants: In a national longitudinal observational study in the United States, individuals who previously participated in a clinical trial for subcutaneous buprenorphine injections for treatment of OUD were enrolled and followed for an average of 4.2 years after participation in the clinical trial. Measurements: We identified recovery subgroups based on psychosocial outcomes including depression, opioid withdrawal and pain. We compared opioid use, treatment utilization and quality of life among these subgroups. Findings Three dimensions of the recovery process were identified: depression, opioid withdrawal and pain. Using these three dimensions, participants were classified into four recovery subgroups: high‐functioning (minimal depression, mild withdrawal and no/mild pain), pain/physical health (minimal depression, mild withdrawal and moderate pain), depression (moderate depression, mild withdrawal and mild/moderate pain) and low‐functioning (moderate/severe withdrawal, moderate depression and moderate/severe pain). Significant differences among subgroups were observed for DSM‐5 criteria (P < 0.001) and remission status (P < 0.001), as well as with opioid use (P < 0.001), treatment utilization (P < 0.001) and quality of life domains (physical health, psychological, environment and social relationships; Ps < 0.001, Cohen's fs ≥ 0.62). Recovery subgroup assignments were dynamic, with individuals transitioning across subgroups during the observational period. Moreover, the initial recovery subgroup assignment was minimally predictive of long‐term outcomes. Conclusions: There appear to be four distinct subgroups among individuals in recovery from OUD. Recovery subgroup assignments are dynamic and predictive of contemporaneous, but not long‐term, substance use, substance use treatment utilization or quality of life outcomes.